Electromyographic activation patterns during swallowing in older adults - Jin Young Ko (Nature Portfolio, 2021)
Abstract Age-related weakness due to atrophy and fatty infiltration in oropharyngeal muscles may be related to dysphagia in older adults. However, little is known about changes in the oropharyngeal muscle activation pattern in older adults. This was a prospective and experimental study. Forty healthy participants (20 older [> 60 years] and 20 young [< 60 years] adults) were enrolled. Six channel surface electrodes were placed over the bilateral suprahyoid (SH), bilateral retrohyoid (RH), thyrohyoid (TH), and sternothyroid (StH) muscles. Electromyography signals were then recorded twice for each patient during swallowing of 2 cc of water, 5 cc of water, and 5 cc of a highly viscous fluid. Latency, duration, and peak amplitude were measured. The activation patterns were the same, in the order of SH, TH, and StH, in both groups. The muscle activation patterns were classified as type I and II; the type I pattern was characterized by a monophasic shape, and the type II comprised a pre-reflex phase and a main phase. The oropharyngeal muscles and SH muscles were found to develop a pre-reflex phase specifically with increasing volume and viscosity of the swallowed fluid. Type I showed a different response to the highly viscous fluid in the older group compared to that in the younger group. However, type II showed concordant changes in the groups. Therefore, healthy older people were found to compensate for swallowing with a pre-reflex phase of muscle activation in response to increased liquid volume and viscosity, to adjust for age-related muscle weakness.